2001
DOI: 10.1079/ber2001102
|View full text |Cite
|
Sign up to set email alerts
|

Assessing mating performance of male Glossina pallidipes (Diptera: Glossinidae) using a walk-in field cage

Abstract: To monitor the quality of male tsetse for use in the sterile insect technique (SIT), a field cage test was developed and evaluated. Mating competitiveness was tested with male Glossina pallidipes Austen that emerged from pupae stored for different periods at 15°C. Control males emerged from pupae stored at 23–24°C and emerged at 26.5°C. Each sample of test males was divided into two groups with one group being irradiated at 120 Gy; the other group was not irradiated. More than 70% of the maximum possible numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 19 publications
5
65
0
Order By: Relevance
“…It was showed that a dose of 120 Gy did not affect mating competitiveness of G . pallidipes males in walk-in field cages and keeping the irradiated pupae for 24–72 h at a low temperature of 15°C even increased the competitiveness of the emerged males [37]. …”
Section: Introductionmentioning
confidence: 99%
“…It was showed that a dose of 120 Gy did not affect mating competitiveness of G . pallidipes males in walk-in field cages and keeping the irradiated pupae for 24–72 h at a low temperature of 15°C even increased the competitiveness of the emerged males [37]. …”
Section: Introductionmentioning
confidence: 99%
“…The netting cage [26] was cylindrical, 2.9 m in diameter and 2.0 m high [27,28]. The field cage was erected inside a greenhouse under natural light without environmental controls for the age group experiments.…”
Section: The Field Cage and Its Environmentmentioning
confidence: 99%
“…In the absence of such interference from a rival, single irradiated males initiated copulation much more quickly. Similar male-male interference has also been observed in more natural, field-cage conditions (Mutika et al 2001).…”
mentioning
confidence: 63%
“…An increase in copulation duration can occur in irradiated male potato-tuber moths, and the females may re-mate more quickly after mating with irradiated males (Saour and Makee, 1999). Mutika et al (2001) found that, in general, irradiated male G. pallidipes copulated for longer and transferred fewer sperm than the non-irradiated males. Although the success on Unguja Island indicated that sterilized G. austeni can compete successfully, the effects on irradiation on the mating behaviour of male G. austeni are not well known.…”
mentioning
confidence: 96%
See 1 more Smart Citation